Project-Based Learning Based on Islamic Values in Learning Tools on Bacteria Material in High School: An Efforts to Improve Students' Learning Motivation - Syahril, Sulthan (Global Education Journal, 2025)
Although students are usually self-motivated, external factors are still needed to increase their learning motivation. Pre-survey results indicate that schools do not use project-based learning models when teaching. This study aims to implement Islamic values-based project-based learning in learning materials on bacteria in high schools: an effort to increase student learning motivation. This research method is a Research and Development (R&D) using the ADDIE Model with a non-equivalent control group design to differentiate between the experimental and control classes through pretests and posttests. This research was conducted at SMA Muhammadiyah 2 Bandar Lampung during the 2022/2023 academic year. The population of this study was all tenth-grade students, with sampling carried out using cluster random sampling. The data collection technique used tests administered twice, namely pretests and posttests. Data analysis techniques to determine whether there is an effect of the use of the Project-Based Learning approach model on student learning motivation were carried out using the T-test and N-Gain. The results of the analysis indicate that the development of the Islamic values-based Project-Based Learning model is suitable for learning on bacteria material and has a simultaneous positive effect on increasing student learning motivation.